Social Construction of Beauty Symbols in 2024 Legislative Candidate News - Vivi Aniq Auvia Hidayani (Journal of Feminism and Gender Studies, 2025)
Women’s involvement in the political stage is still not optimal because they are objects of construction in a patriarchal culture. A construction of beauty is represented through the 2024 Election news media. This research aims to determine the extent to which the media constructs symbols of beauty for women running in the general election. This study uses qualitative methods. The samples from this research are four viral news stories about female legislative candidates from different online news media. By using the framing analysis of the Pan and Kosicki model from the theory of Zhongdang Pan and Gerald M. Kosicki, it was found that there is a construction of beauty that is someone who has a white appearance, no acne, light natural make-up, wears a hijab, has neat teeth, and has a beautiful smile. Beauty is then constructed as a reason for people to vote in elections, overriding attention and encouraging individuals to act on the initiative of first impressions.